(NiSTORIQ PARADOKSA gIBBSA (B/s - (NhAJTUN(B, (NsERGEJ dAWYDOWI^s; (NaLEKSEEW(B, (Ni(B.(Ns(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 157-162 (185 (NNAZW(B.)s
(Nan sssr(B, (NiN(B-(NT ISTORII ESTESTWOZNANIQ I TEHNIKIs
Keywords: (NgIBBSA PARADOKSs